Shaken Baby Syndrome: Diagnosis, treatment, prevention, through a multidisciplinary approach - Průchová, Dominika (Society of Integrated Sciences, 2013)
The incidence of shaken baby syndrome (SBS) has been mapped in detail in a number of advanced countries throughout the world, with very detailed data being available from the USA, New Zealand, Japan, etc. Unfortunately, data related to the prevalence of this syndrome are not available in the Czech Republic. It is estimated that 21-74/100,000 children worldwide fall victim every year. SBS refers to a collection of symptoms that occur in children traumatized by being shaken. Most frequently, the victims are infants younger than one year of age, usually between 5 and 6 months old. The damage is primarily neurological in nature when brain tissue, blood vessels and nerve junctions are traumatized. The characteristic clinical findings in shaken baby syndrome are retinal hemorrhage and subdural or subarachnoid bleeding with no external evidence of head injury. The biomechanics of such trauma are also well understood. Victims of SBS suffer high morbidity and mortality rates, particularly in infants younger than six months of age. Children who survive SBS often develop long-term consequences, the nature of which depends on the degree of trauma sustained. Such consequences require long-term monitoring and treatment by a multidisciplinary team of experts actively involved in the process from the time of the child?s admission to hospital. The role these physicians, medical staff and medical social workers play in the recovery process is both invaluable and irreplaceable. The aim of this publication is to provide a comprehensive overview of shaken baby syndrome in response to related research that has been published abroad. A large portion will be dedicated to the diagnosis and long-term treatment of the consequences resulting from SBS, as provided through the cooperation of the multidisciplinary team.
SYNDROM TŘESENÉHO DÍTĚTE: diagnostika, léčba, prevence, multidisciplinární přístup
Keywords: shaken baby syndrome; neurological complications; brain damage; retinal hemorrhage; multidisciplinary team.; syndrom třeseného dítěte; neurologické komplikace; poškození mozku; krvácení do sítnice; multidisciplinární tým